Diminished platelet aggregation in patients with iron deficiency anemia - Çaliskan, Ü; Öner, AF; Kabakus, N; Koç, H (Lippincott Williams & Wilkins, 1999)
To evaluate platelet function in iron deficiency anemia, using impedance (in whole blood) and optic tin platelet-rich plasma methods, platelet aggregation analyses were performed in 42 children with iron deficiency anemia at the time of diagnosis and after iron therapy. Collagen-induced platelet aggregation was decreased in patients before therapy compared to after therapy and control levels as indicated by the two methods while adenosine diphosphate (ADP)-induced platelet aggregation was decreased only by the whole blood method. Platelet aggregation with epinephrine, performed only by the optic method, was not altered in patients with iron deficiency anemia. Platelet counts were found to be increased in patients with iron deficiency anemia, and decreased with therapy. These results indicate that some platelet functions are decreased in patients with iron deficiency anemia. These decreased functions may be compensated by increased platelet numbers.
Keywords: iron deficiency; platelet; children